4u-8+2(2u+2)=-4(u+5)

Simple and best practice solution for 4u-8+2(2u+2)=-4(u+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4u-8+2(2u+2)=-4(u+5) equation:


Simplifying
4u + -8 + 2(2u + 2) = -4(u + 5)

Reorder the terms:
4u + -8 + 2(2 + 2u) = -4(u + 5)
4u + -8 + (2 * 2 + 2u * 2) = -4(u + 5)
4u + -8 + (4 + 4u) = -4(u + 5)

Reorder the terms:
-8 + 4 + 4u + 4u = -4(u + 5)

Combine like terms: -8 + 4 = -4
-4 + 4u + 4u = -4(u + 5)

Combine like terms: 4u + 4u = 8u
-4 + 8u = -4(u + 5)

Reorder the terms:
-4 + 8u = -4(5 + u)
-4 + 8u = (5 * -4 + u * -4)
-4 + 8u = (-20 + -4u)

Solving
-4 + 8u = -20 + -4u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '4u' to each side of the equation.
-4 + 8u + 4u = -20 + -4u + 4u

Combine like terms: 8u + 4u = 12u
-4 + 12u = -20 + -4u + 4u

Combine like terms: -4u + 4u = 0
-4 + 12u = -20 + 0
-4 + 12u = -20

Add '4' to each side of the equation.
-4 + 4 + 12u = -20 + 4

Combine like terms: -4 + 4 = 0
0 + 12u = -20 + 4
12u = -20 + 4

Combine like terms: -20 + 4 = -16
12u = -16

Divide each side by '12'.
u = -1.333333333

Simplifying
u = -1.333333333

See similar equations:

| 14X+98=8X+62 | | 52=4x+1 | | 4x^2+5(4x^2-x)-4x= | | 5(3q+87)=15q-435 | | 2y+20= | | -3(2v-4)+2v=6(v+3) | | 22/b=11/3 | | -18X-129=-9X-84 | | -6X+14=-4X+8 | | 4g+3=1 | | -21X-75=-14X-47 | | 2x+3x^2=4 | | 10X+81=5X+51 | | 17X-72=11X-48 | | 3(w-7)-6=-3(-9w+7)-9w | | -21X-217=-12X-136 | | -12X-217=-12X-136 | | -11X-9=-7X-5 | | -19X-51=-12X-30 | | 8x-12=20x | | (2x+75)=(4x-25) | | 1+2(5x-3)=-2(6x-5)+4x | | (4x+18)=(7x-72) | | 4t^2-14t+35=0 | | -3X+7=-2X+4 | | 3/8*x=21/2 | | 4g+3=1g | | 3-2x=1000x | | 37w^2-312w-192924=0 | | (82.4-52)3/5=x | | -5X+13=-3X+7 | | (84.4-52)3/5=x |

Equations solver categories